Comparison of different modelling strategies for the representation of non linear response of RC columns subjected to biaxial loading - Rodrigues, H. (2011)
Aiming at studying the performance of different non-linear modelling strategies for RC columns subjected to axial load and cyclic biaxial horizontal loading, several analyses were developed using the computer code SeismoStruct. This study comprised the simulation of 24 cantilever RC columns quasi-statically tested under constant axial force and cyclic uniaxial and biaxial displacements imposed with different loading paths. The results show that all adopted modelling strategies (distributed-inelasticity and lumped-plasticity) lead to similar accuracy in terms of restoring shear-force evolution. Generically, they were found suitable for accurately predicting the cyclic response of RC columns, with standard material parameters, although the models may not succeed in representing the strength degradation for cyclic loading.